2022
DOI: 10.1155/2022/1460945
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Susceptible Watershed to Sediment Yield and Evaluation of Best Management Practice: A Case Study of Awata River, Southern Ethiopia

Abstract: Soil erosion is currently a global problem that causes land degradation and long-lasting challenges in Ethiopia. Sediment yield is influenced by the watershed characteristics such as land cover, soil class, and slope, which are considered the drivers of soil erosion in the basin. The middle Awata watershed is highly susceptible to soil erosion due to its topographical features. This study is therefore aimed at estimating sediment yield, examining its spatial distribution, and evaluating the selected Best Manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The corresponding mean annual sediment yield contribution of each subbasin is shown in Table 9. The estimated sediment yield in the Genale Dawa-3 dam watershed was consistent with that of other studies done in other basins in Ethiopia, including the studies by [30] in the Finchaa catchment [33], in the Awata watershed [36], in the Bilate watershed [37], in the Megech reservoir catchment [38], in the Welmel watershed, and [39] in the Toba watershed in Ethiopia.…”
Section: Sediment Yield Rate Of Genale Dawa-3 Dam Watershedsupporting
confidence: 89%
See 1 more Smart Citation
“…The corresponding mean annual sediment yield contribution of each subbasin is shown in Table 9. The estimated sediment yield in the Genale Dawa-3 dam watershed was consistent with that of other studies done in other basins in Ethiopia, including the studies by [30] in the Finchaa catchment [33], in the Awata watershed [36], in the Bilate watershed [37], in the Megech reservoir catchment [38], in the Welmel watershed, and [39] in the Toba watershed in Ethiopia.…”
Section: Sediment Yield Rate Of Genale Dawa-3 Dam Watershedsupporting
confidence: 89%
“…The PBIAS result shows the model had a slight overestimation (negative) during the calibration and an underestimation (positive) during the validation. Hence, the statistical model performance indicators at the Genale Dawa-3 dam watershed were slightly high in comparison to those estimated by various studies conducted in different parts of Ethiopia [28,[30][31][32][33]. The difference may be due to the soil, land use, and slope steepness in the study areas.…”
Section: Model Parameter Sensitivity Analysis For Streamflowmentioning
confidence: 54%
“…Contouring is a type of tillage that helps mitigate soil erosion by slowing surface runoff and allowing it to penetrate by impounding it [ 41 ]. This scenario assessed contouring in agricultural lands by modifying the soil conservation service curve number (CN2) and USLE Practice factor (USLE_P) in SWAT based on the land slope, literature reports, and SWAT user manual recommendations [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Kefay et al [ 44 ] confirmed that the SWAT could quantify sediment with its spatial distribution as well as identify hotspot areas for prioritization management approaches in Ethiopia. However, without hydrological models, it is difficult to quantify the intricate interactions between hydrological variables and evaluate the anthropogenic impacts on changes in sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it lies within the acceptable limit, which is verified through statistical tools for model performance evaluation. The simulation assumes that erosion is conducted through a natural process by considering well‐known erosion factors, such as soil, rainfall, slope length, slope steepness, land use, and management characteristics of the watershed (Amdihun et al, 2014; Kefay et al, 2022). It is used to gain insight into the system operation and interaction impact of all factors on erosion in a way that allows us to see the impact of each factor by identifying sensitive factors that govern the gross output and answer “what if” questions by omitting and including each factor without disturbing the natural system, which is difficult to conduct in a real manner.…”
Section: Introductionmentioning
confidence: 99%